2012
DOI: 10.1590/s0103-51502012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Abordagem fisioterapêutica do linfedema bilateral de membros inferiores

Abstract: ResumoIntrodução: O linfedema é um acúmulo de proteína no interstício em virtude de de iciência do sistema linfático, sendo recomendada a utilização da Terapia Física Complexa como forma de tratamento. Objetivo: Veri icar os efeitos da Terapia Física Complexa no tratamento e na manutenção do linfedema bilateral de membros inferiores. Métodos: Participaram deste estudo sete pacientes com linfedema bilateral nos membros inferiores, de faixa etária entre 59 e 85 anos, os quais foram submetidos a: 1ª avaliação isi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
(63 reference statements)
2
9
0
3
Order By: Relevance
“…Similar results were found by Tacani et al 20 , who observed reduction of lymphedema at all points measured in the treated lower limb. The authors treated two groups: one with four patients, who received manual lymphatic drainage and elastic restraint once a week; another group with three patients, who received CDT twice a week.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were found by Tacani et al 20 , who observed reduction of lymphedema at all points measured in the treated lower limb. The authors treated two groups: one with four patients, who received manual lymphatic drainage and elastic restraint once a week; another group with three patients, who received CDT twice a week.…”
Section: Discussionsupporting
confidence: 91%
“…IG received CDT [18][19][20][21] twice weekly in 50-minute sessions consisting of manual lymphatic drainage, kinesiotherapy, leg bandaging with lymphedema (up to knee height), and limb care and hygiene guidelines. Manual lymphatic drainage was applied by the same physiotherapist in all sessions, using the Foldi technique 18 .…”
Section: Intervention Protocolmentioning
confidence: 99%
“…It is known that lymphedema affects people of a range of different ages and of both sexes. It primarily occurs among women, 2 as confirmed in this study, in which the sample was predominantly female (72%). This is similar to two other studies, in which samples comprised 70.7% and 77% women.…”
Section: Discussionsupporting
confidence: 76%
“…It affects around 15% of the global population. 1,2 Lower limb (LL) lymphedema is the most prevalent presentation, accounting for 80% of cases. 2,3 In addition to limb swelling, other very common complaints among patients with lymphedema are pains, reduced amplitude of movement, infections, and problems with body image.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation